Income Redistribution and Socio-economic Development - Beáta Mikušová Mericková; Renáta Halásková (Review of Economic Perspectives, 2014)
The trade off efficiency and equity issue, which is represented by income redistribution, becomes increasingly debated not only in economic and social, but also in political dimension. Solution of this trade-off problem is projected into the implementation of social policy and results achieved in macroeconomics policy, with the goal to define the optimal scope and character of the income redistribution processes. The submitted empirical study responds to this problem through the investigation of research question focused on the existence of a relationship between the social protection expenditure (expenditure on policy of family, old age and unemployment) and the achieved level of socio-economic development (quantified by Human Development Index HDI). The existence of this relationship is statistically tested in a sample of 15 countries. The research sample is heterogeneous in relation to the analyzed indicators, and it contains countries with a different level of economics development and income redistribution policy. Based on the results of quantitative analysis in most surveyed countries, impact of social protection expenditure on the reached level of economic development was confirmed. The correlation between the social protection expenditure and socio-economic development is positive in the case of the family and old-age pension policy, and negative in the case of employment policy
Keywords: 330